Auxin Signaling in Regulation of Plant Translation Reinitiation - Schepetilnikov, Mikhail; Ryabova, Lyubov A. (Frontiers in Plant Science, 2017)
The mRNA translation machinery directs protein production, and thus cell growth, according to prevailing cellular and environmental conditions. The target of rapamycin (TOR) signaling pathway—a major growth-related pathway—plays a pivotal role in optimizing protein synthesis in mammals, while its deregulation triggers uncontrolled cell proliferation and the development of severe diseases. In plants, several signaling pathways sensitive to environmental changes, hormones and pathogens have been implicated in post-transcriptional control, and thus far phytohormones have attracted most attention as TOR upstream regulators in plants. Recent data have suggested that the coordinated actions of the phytohormone auxin, Rho-like small GTPases from plants (ROPs), and TOR signaling contribute to translation regulation of mRNAs that harbor upstream open reading frames (uORFs) within their 5’-untranslated regions (5’-UTRs). This review will summarize recent advances in translational regulation of a specific set of uORF-containing mRNAs that encode regulatory proteins—transcription factors, protein kinases and other cellular controllers—and how their regulation can impact plant growth and development.